The image of the hero in modern Ukrainian cinema. Interview with Dmytrо Sukholytkyy-Sobchuk - Tymoshenko, Alyona (Ukrainian Cultural Studies, 2024)
His feature film debut was Pamphyr (2022), which had its world premiere at the Cannes Film Festival. The film was nominated for the EFA Prize for Best First Feature and won more than 30 awards at over 70 festivals. His short films have been selected for the most prestigious festivals, including Sundance Film Festival, DOC NYC, IDFA, Toronto International Film Festival, Clermont-Ferrand International Short Film Festival, Palm Springs International Festival of Short Films and others. He is a member of the Ukrainian (since 2017) and European (since 2018) film academies, the founder and organiser of the Terrarium screenwriting platform.